Numerical study of convective heat transfer and particle distribution subject to magneto-static field in a square cavity - Shi, Lei; Tao, Wenliang; Zheng, Nianben; Zhou, Tian; Sun, Zhiqiang (International journal of thermal sciences, 2023)
Magnetic nanoparticle suspension has been applied in a variety of energy transport systems due to its excellent flowing characteristics and extraordinary thermal conductivity, and it has proven to significantly influence the sustainable development of energy and the environment. This work aims to focus on the thermal, fluidic properties of the magnetic nanofluid while also considering the coupling factors of magnetic field, thermal exchange, fluidity and nanoparticle concentration. Firstly, the simulation results of velocity and temperature distribution will be validated using the finite element method, which is in accordance with previous results of natural convection in a square cavity. The analysis model of developed magneto-hydrodynamics heat transfer will then be constructed with the explanation of entropy and concentration distribution. In comparison to natural convection, the magnetic field-enhanced method is able to break through the limit of thermal exchange efficiency. In addition, when the magnetic field is increased to 30 kA/m, the thermodynamic force is replaced by magnetic volumetric force and this plays a role in the heat transfer of the cavity, while the average Nusselt numbers increase by 17% in comparison to natural convection performance (Ra = 105). Entropy generation increases as magnetic field strength increases as a result of the enhancement to circulation and temperature gradient in the nanofluid. This work utilises an advanced strategy for the convection performance of magnetic nanofluid and analyses the multi-physical field. •The magneto-thermal-flow-concentration multi-physical field coupling transport model is built.•The transformation process from natural convection to magnetic convection is investigated.•Entropy and concentration distribution in magneto-hydrodynamics heat transfer are researched.